Analysis of Factors Affecting The Income of Coffee Shop Msmes in Denpasar City - Ni Kadek Eva Pridariasih; Ni Putu Martini Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The Micro, Small, and Medium Enterprises (MSMEs) sector plays a crucial role in economic development by helping to reduce inequality resulting from uneven development processes. This study aims to analyze the simultaneous and partial effects of capital, price, working hours, facilities, and promotion on income, as well as to examine the moderating role of promotion on the effect of price on the income of coffee shop MSMEs in Denpasar City. The sample consisted of 85 coffee shop MSMEs selected using simple random sampling. The data analysis technique employed was moderated regression analysis (MRA). The results show that simultaneously, capital, price, working hours, facilities, and promotion significantly affect the income of coffee shop MSMEs in Denpasar. Partially, each of these variables—capital, price, working hours, facilities, and promotion—has a significant positive influence on income. Coffee shops equipped with complete facilities tend to earn higher income compared to those with fewer amenities. The findings also reveal that coffee shops utilizing promotional strategies generate higher income than those that do not. It is recommended that coffee shop MSME operators focus on long-term promotional strategies to build customer loyalty and increase income.